Bioresorbable fibers for interstitial null-separation diffuse optical spectroscopy using fast temporal gating - Vamshi Damagatla; Nadia G Boetti; Laura Di Sieno; Diego Pugliese; Ilaria Bargigia; Davide Janner; Alberto Dalla Mora; Antonio Pifferi (JPhys Photonics)
Bioresorbable fibers are an exciting prospect as probes and implants to provide optical access to the human body. In this work, we demonstrate interstitial spectroscopy with bioresorbable fibers at null distance, using time-domain diffuse optics that disentangles absorption from scattering properties and probes the tissues up to a depth of a few cm around the fiber tips. We exploit a fast-gated single-photon avalanche diode with $\gt$ 55 dB of dynamic range to overcome the burst of ‘early’ photons hiding the information of absorption from deep tissues. We tested the absorption linearity—retrieving the water spectrum in the 700–950 nm range with $\gt$ 85% accuracy over two decades of absorption change—and verified the hypothesis of a scattering-independent absorption retrieval. Further, we were able to detect spectral changes at a distance of 1 cm from an inclusion embedded in a biological tissue. Time-domain diffuse optical spectroscopy with bioresorbable fibers could detect spectral changes without being affected by blood extravasation at the fiber tips and could help for long-term monitoring in tissue healing, thermal treatment, photodynamic therapy and ultimately, towards minimally invasive medical procedures.